Intention of Stock Investment by Students in The Covid-19 Period - Fajar Ari Wicaksono; Muhammad Jihadi; Widayat widayat (Business Innovation Management and Entrepreneurship Journal, 2022)
This research is intended to know and prove attitudes to risk and return on investment in investment intentions made by students with financial literacy and investment understanding as moderation.The type of research used is explanatory research, with a quantitative approach of data collection using questionnaires with the number of respondents to 277 students of the Faculty of Economics and Business, University of Muhammadiyah Malang class of 2019. Furthermore, the analysis of data that has been obtained using the Structural Equation Model (SEM) method in the SmartPLS program. The results of the analysis showed that attitudes to risk and return have a positive effect on investment intentions while financial literacy and investment understanding can moderate perceptions of risk and returns on investment intentions positively and significantly.